New Frontiers in Paleopedology and Terrestrial Paleoclimatology: Paleosols and Soil Surface Analog Systems 2013
DOI: 10.2110/sepmsp.104.01
|View full text |Cite
|
Sign up to set email alerts
|

Paleoclimatic Applications and Modern Process Studies of Pedogenic Siderite

Abstract: Pedogenic siderite is a carbonate mineral that forms in the reducing groundwaters of poorly drained soils and paleosols in zonal climatic belts with strongly positive precipitation-evaporation balances. Microcrystalline and spherulitic forms of siderite are commonly recognized in micromorphologic studies of hydromorphic paleosols. Ancient paleosol sphaerosiderites commonly occur with diameters in excess of 1 mm, while modern pedogenic siderite crystal dimensions in excess of 100 lm are rare. Pedogenic siderite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Sphaerosiderite is a finely crystalline, millimeter-scale spherulitic form of siderite that occurs in a broad spatial and temporal range of paleosols (Ludvigson et al 2013). Ludvigson et al (1998) demonstrated that sphaerosiderites within a paleosol profile typically record a small range of δ 18 O values (less than ∼2 ) and a large range of δ 13 C values (up to >30 ); δ 13 C variability is interpreted to represent the range of microbial metabolic pathways present in poorly drained soils, whereas uniform δ 18 O values are interpreted to represent soil or meteoric water δ 18 O values during crystallization.…”
Section: Meteoric Sphaerosiderite Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphaerosiderite is a finely crystalline, millimeter-scale spherulitic form of siderite that occurs in a broad spatial and temporal range of paleosols (Ludvigson et al 2013). Ludvigson et al (1998) demonstrated that sphaerosiderites within a paleosol profile typically record a small range of δ 18 O values (less than ∼2 ) and a large range of δ 13 C values (up to >30 ); δ 13 C variability is interpreted to represent the range of microbial metabolic pathways present in poorly drained soils, whereas uniform δ 18 O values are interpreted to represent soil or meteoric water δ 18 O values during crystallization.…”
Section: Meteoric Sphaerosiderite Linesmentioning
confidence: 99%
“…Ludvigson et al (1998) demonstrated that sphaerosiderites within a paleosol profile typically record a small range of δ 18 O values (less than ∼2 ) and a large range of δ 13 C values (up to >30 ); δ 13 C variability is interpreted to represent the range of microbial metabolic pathways present in poorly drained soils, whereas uniform δ 18 O values are interpreted to represent soil or meteoric water δ 18 O values during crystallization. Over the past two decades, a series of mid-Cretaceous sphaerosiderite lines have been generated over paleolatitudes ranging from the paleoequator to ∼70 • N (Ludvigson et al 2013), the results of which suggest a more pronounced greenhouse hydrological cycle (Suarez et al 2011b) than predicted by general circulation models (Poulsen et al 2007). …”
Section: Meteoric Sphaerosiderite Linesmentioning
confidence: 99%
“…The other form of rhodochrosite cement, microspherules, exhibits the same size and development as spherosiderites that form in humid continental settings within water‐logged soils, and are often associated with roots decomposing in phreatic environments (e.g. Ludvigson et al ., , ). The conditions in the Orava‐Nowy Targ basin were also characterized by a humid climate and water‐logged soils, as discussed above.…”
Section: Discussionmentioning
confidence: 97%
“…Both siderite and rhodochrosite exhibit a relatively small spread of δ 18 O values ( ca 1·5‰) which is probably related to temperature variations and, therefore, indicates formation during very shallow burial where seasonality is not buffered (cf. Ludvigson et al ., ). The δ 18 O values of rhodochrosite are slightly lower than those of siderite, suggesting a rather higher temperature of formation, probably at slightly shallower depth.…”
Section: Discussionmentioning
confidence: 99%
“…, , Gautier , Postma , Mozley , b, Curtis ); (b) as siderite nodules in wetland soils and sediments of the globe's humid climatic belts (Ludvigson et al . , , Ufnar et al . , Sheldon and Tabor , Tabor and Myers ); (c) as cements in sandstones and mudstones (Macquaker et al .…”
mentioning
confidence: 99%